Gluten-Associated Neurological Disorders: A Cases Series - Vismaya S. Bachu; Farinaz Ghodrati; Brent L. Fogel; Guy A. Weiss (Case Reports in Gastroenterology)
Introduction: Gluten-associated disorders, including celiac disease (CeD) and non-celiac gluten sensitivity (NCGS), can present with various extraintestinal neurologic manifestations, including sensory neuropathy, ataxia, headaches, and seizures. Case Presentations: In this case series, we present 3 interesting patients with gluten-associated neurological disorders (GAND) across a spectrum of gluten-associated disorders severity, from gluten sensitivity, to CeD, to refractory CeD, illustrating variable presentations and treatment approaches for this underdiagnosed population. Conclusion: For many patients with neurological presentations who initially lack gastrointestinal symptoms, diagnosis remains challenging. Once diagnosed, while a gluten-free diet has been the mainstay of treating GAND for many years, this approach may only prevent progression of disease without reversal of symptoms. Further studies are needed to help guide the development and standardization of treatments for this patient population.